5(3x+2)=17x-2

Simple and best practice solution for 5(3x+2)=17x-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(3x+2)=17x-2 equation:


Simplifying
5(3x + 2) = 17x + -2

Reorder the terms:
5(2 + 3x) = 17x + -2
(2 * 5 + 3x * 5) = 17x + -2
(10 + 15x) = 17x + -2

Reorder the terms:
10 + 15x = -2 + 17x

Solving
10 + 15x = -2 + 17x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-17x' to each side of the equation.
10 + 15x + -17x = -2 + 17x + -17x

Combine like terms: 15x + -17x = -2x
10 + -2x = -2 + 17x + -17x

Combine like terms: 17x + -17x = 0
10 + -2x = -2 + 0
10 + -2x = -2

Add '-10' to each side of the equation.
10 + -10 + -2x = -2 + -10

Combine like terms: 10 + -10 = 0
0 + -2x = -2 + -10
-2x = -2 + -10

Combine like terms: -2 + -10 = -12
-2x = -12

Divide each side by '-2'.
x = 6

Simplifying
x = 6

See similar equations:

| -9+x=-21 | | y+8=-1(x+4) | | 5x+7=3x+9 | | 3-3y=9-4y | | (x+7)=(24+26) | | y-1=3(x+6) | | y-5=3(x-1) | | 67-4x=5x+18 | | 8x+v=3x+w | | 8-9x=89-30x | | Y=mx+bx | | y+2=-6(x+6) | | T=3+1.25(13) | | 6x+36=15x-54 | | 6x-5=-3 | | 8y-2=13y+33 | | 5(5x-4)-4(3x-6)= | | -46-2x=8-8x | | -4-6n=7n+3 | | 2x-6x=4x+3 | | T=3+1.25c | | -4n-6=7n+3 | | 3(4x+1)+2(6x-9)= | | 5h-3h+9h=176 | | 12500=.5x^2+11x+4000 | | -4m=28 | | 48=7t-3t | | 7(x+7)+5(2x-8)= | | 2y+5+4y=6y+3 | | -3+7=-10 | | 2x^2=450 | | y+4y=95 |

Equations solver categories